Nutrition : an applied approach - Thompson, Janice , 1962-; Manore, Melinda , 1951- (Boston, Massachusetts : Pearson, 2012)
Includes access code to MyNutritionLab with MyDietAnalysis
1. The role of nutrition in our health -- 2. Designing a healthful diet -- 3. The human body: are we really what we eat? -- 4. Carbohydrates: plant-derived energy nutrients -- 5. Fats: essential energy-supplying nutrients -- 6. Proteins: crucial components of all body tissues -- 7. Nutrients involved in fluid and electrolyte balance -- 8. Nutrients involved in antioxidant function -- 9. Nutrients involved in bone health -- 10. Nutrients involved in energy metabolism and blood health -- 11. Achieving and maintaining a healthful body weight -- 12. Nutrition and physical activity: keys to good health -- 13. Food Safety and technology: impact on consumers -- 14. Nutrition through the life cycle: pregnancy and the first year of life -- 15. Nutrition through the life cycle: childhood to late adulthood
Includes bibliographical references and index
Keywords: Nutrition